(untitled) (Research, Society and Development, 2021)
The child development is a continuous and dynamic transformation, where the nurse becomes essential for the care and guidance that must be provided, encouraging positive practices to promote child health and well-being. The aim of the study is to understand the role of nurses in promoting family bonds and child development. Methods: A descriptive and exploratory study with a qualitative approach was carried out. Data collection was mediated by unstructured, recorded and later transcribed, on the role of nurses in childcare consultation aimed at promoting family bonds and child development, with six nurses from Family Health Units in the city of Recife, in the Health Districts IV and V, from January to March 2020. For data analysis, the descriptive line by line is used, generating codes grouped into two categories, addressing the role of nurses in child development and their perception of care and family bonds. Results: Surveillance of growth and development in healthy children aged zero to two years and the stimulation of positive parenting interactions and practices between caregivers and children, from prenatal care, was verified. The teams’ link with day care centers and educational institutions is not enhanced for child development surveillance. The perception of care and family bonds is made up of intra-family barriers and factors. Conclusion: The results reiterate the need to qualify nurses with creative strategies for permanent education, on a multidisciplinary basis, bringing children and families to the fore.